Penerapan Pembelajaran Tematik Berbasis Budaya Betawi untuk Meningkatkan Logical Intelligence Siswa SD Islam Taman Qur’aniyah Jakarta Selatan - Fery Muhamad Firdaus; Nurul Badriyah (Al Ibtida: Jurnal Pendidikan Guru MI, 2018)
AbstrakPada dasarnya seorang siswa memiliki banyak kecerdasan. Salah satu diantaranya adalah kecerdasan logika. Namun faktanya kecerdasan logika siswa SD Islam Taman Qur’aniyah masih rendah. Salah satu penyebabnya adalah karakteristik siswa yang berbeda-beda dan penggunaan strategi pembelajaran yang kurang inovatif. Penelitian ini bertujuan untuk: (1) mengetahui proses pembelajaran tematik berbasis budaya Betawi, dan (2) meningkatkan kecerdasan logika siswa kelas IV SD Islam Taman Qur’aniyah melalui pembelajaran tematik berbasis budaya Betawi. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK). Metode ini dilakukan dengan empat tahap, yaitu perencanaan, implementasi tindakan, pengaruh implementasi monitor, dan survei/refleksi. Teknik pengumpulan data yang digunakan adalah wawancara, observasi aktvitas guru dan siswa, tes kecerdasan logika, catatan lapangan, dan dokumentasi. Subjek dalam penelitian ini adalah siswa kelas IV SD Islam Taman Qur’aniyah yang berjumlah 27 siswa. Penelitian ini dilaksanakan melalui 3 siklus. Data yang diperoleh kemudian dianalisis menggunakan nilai persentase hasil tes kecerdasan siswa. Hasil Penelitian ini menunjukkan bahwa persentase hasil tes kecerdasan logika yang diperoleh pada siklus I sebesar 41%  siswa dengan nilai rata-rata 57. Sementara itu pada siklus II meningkat menjadi 70% siswa dengan nilai rata-rata 69 dan kembali meningkat hingga mencapai 85% siswa pada siklus III dengan nilai rata-rata 77. Dengan demikian dapat disimpulkan bahwa penerapan pembelajaran tematik berbasis budaya Betawi dapat meningkatkan kecerdasan logika siswa.Kata kunci: pembelajaran tematik, budaya betawi, kecerdasan logikaAbstractBasiclly a student has a lot of intelligence. One of them is logical intelligence. But in fact the logical intelligence of islamic elementary school’s students of Qur'aniyah is still low. One of the causes is, the characteristics of different students, and the use of less innovative learning strategies. This study aims to: (1) to know the thematic teaching process based on Betawi culture, and (2) to improve the logical intelligence of fourth grade students of Islamic Elementary School Quraniyah through Betawi based thematic learning. This research uses Class Action Research method (PTK). This method is done with four stages, namely planning, action implementation, influence of monitor implementation, and survey/reflection. Data collection techniques used is interview, teacher’s and student’s activity observation, logic intelligence test, field notes, and documentation. The subjects of the study were the fourth graders of Islamic Elementary School Quraniyah which amounted to 27 students. This study was conduct for 3 cycles. Data obtained then analyzed using percentage value of students intelligence test results. The results of this study indicate that the percentage of logic intelligence test results obtained in the first cycle by 41% of students with an average value of 57. Meanwhile in cycle II increased to 70% of students with an average value of 69 and again increased to 85% of students in cycle III with an average value of 77. Thus can it is concluded that the implementation of thematic learning based on Betawi culture can improve the logical intelligence of students.Keywords: thematic learning, betawi culture, logical intelligenceBasiclly a student has a lot of intelligence. One of them is logical intelligence. But in fact the logical intelligence of islamic elementary school’s students of Qur'aniyah is still low. One of the causes is, the characteristics of different students, and the use of less innovative learning strategies. This study aims to: (1) to know the thematic teaching process based on Betawi culture, and (2) to improve the logical intelligence of fourth grade students of Islamic Elementary School Quraniyah through Betawi based thematic learning. This research uses Class Action Research method (PTK). This method is done with four stages, namely planning, action implementation, influence of monitor implementation, and survey/reflection. Data collection techniques used is interview, teacher’s and student’s activity observation, logic intelligence test, field notes, and documentation. The subjects of the study were the fourth graders of Islamic Elementary School Quraniyah which amounted to 27 students. This study was conduct for 3 cycles. Data obtained then analyzed using percentage value of students intelligence test results. The results of this study indicate that the percentage of logic intelligence test results obtained in the first cycle by 41% of students with an average value of 57. Meanwhile in cycle II increased to 70% of students with an average value of 69 and again increased to 85% of students in cycle III with an average value of 77. Thus can it is concluded that the implementation of thematic learning based on Betawi culture can improve the logical intelligence of students.Keywords: thematic learning, betawi culture, logical intelligence <w:LsdException Locked="false" Priorit